A influência da água na composição de primers autocondicionantes experimentais - Lima, Giana da Silveira (2007)
To investigate the influence of different water concentrations in self-etching primers solvents on microtensile bond strength (μTBS) of an experimental adhesive system. Five experimental self-etching primers with 0, 5, 10, 20 and 40 water concentration (wt %) in solvent, were synthesized. Clearfil SE Bond (CSEB) was used as commercial adhesive. Sixty bovine incisive were randomize separated in six groups (n=20). Vestibular enamel was removed to expose the superficial coronal dentin, this surface was polished wet to create a standardized smear layer. After rinsing, water was removed, leaving the surface visibly dried. The dentin surfaces were etched with primer and air-dried, after coating adhesive resin was applied and photo-activated, following the composite resin restoration was accomplished. After storage for 24 hours, the specimens were sectioned with a refrigerated diamond saw at low-speed. Microtensile bond strength were measured and data were analyzed by one-way ANOVA/Tukey s test (α=0.05). Analysis of variance showed that primer composition was a significant factor for bond strength. There was not difference on bond strength of the primers with water concentration: 40% (53.9 ± 12.7 MPa), 20% (51.1 ± 11.5 MPa) and 10% (47.5 ± 11.4 MPa) and CSEB (52.44 ± 13.27 MPa). The group with 5% (38.6 ± 12.9 MPa) and 0% (31.5 ± 7.5 MPa), present similar bond strength amongst themselves but statistically smaller that the other groups. The water concentration, present in the primer solvent, exercise significant influence on the bond strength of this experimental self-etching adhesive system